PERAN RHO KINASE INHIBITOR DALAM PENATALAKSANAAN GLAUKOMA: STUDI PUSTAKA KOMPREHENSIF MEKANISME, EFIKASI DAN EFEK SAMPING - Wilson Christianto Khudrati; Evelyn Komaratih; Titiek Ernawati; Maria Jessica Rachman (Universitas Ciputra Surabaya, 2023)
Glaucoma ranks as the second-leading contributor to visual impairment, affecting a population of more than 76 million people worldwide. Glaucoma drugs currently work to reduce intraocular pressure (IOP) by reducing the production of aqueous humor (AH) in the ciliary corpus or increasing the drainage of AH through conventional or uveoscleral-uveovortex pathways. The newest hypotensive eye medicine, the Rho Kinase Inhibitor (ROCK), works to reduce TIO with the ROCK inhibitor. In addition, the use of ROCK inhibitors has been shown to be beneficial in the treatment of glaucoma, corneal endothelial healing, and progressive diabetic retinopathy. Although there is evidence that the use of Rho kinase-related inhibitors can cause conjunctive hyperemia, before the discovery of the ROCK inhibitor, there was no anti-glaucoma drug that could work with the trabecular meshwork targets, so ROCK is a very promising therapy for glaucoma patients as TM is responsible for 75% of the AH flow.